Impact of Sonic Hedgehog Pathway Expression on Outcome in HPV Negative Head and Neck Carcinoma Patients after Surgery and Adjuvant Radiotherapy. - Elisabeth Enzenhofer; Thomas Parzefall; Georg Haymerle; Sven Schneider; Lorenz Kadletz; Gregor Heiduschka; Johannes Pammer; Felicitas Oberndorfer; Fritz Wrba; Benjamin Loader; Matthäus Christoph Grasl; Christos Perisanidis; et al. (PLoS ONE, 2016)
HPV positive patients suffering from head and neck cancer benefit from intensified radiotherapy when applied as a primary as well as an adjuvant treatment strategy. However, HPV negative patients treated with surgery and adjuvant radiotherapy lack validated prognostic biomarkers. It is therefore important to define prognostic biomarkers in this particular patient population. Especially, ´high-risk groups´ need to be defined in order to adapt treatment protocols. Since dysregulation of the sonic hedgehog pathway plays an important role in carcinogenesis, we aimed to assess whether members of the sonic hedgehog-signaling pathway may act as prognostic factors in patients with HPV negative head and neck squamous cell carcinoma.In this prospective study, pretreatment tumor biopsies of patients with head and neck squamous cell carcinoma were taken during panendoscopy (2005 to 2008). All patients were treated with surgery and postoperative radiotherapy. After assessment of HPV and p16 status, protein expression profiles of the Sonic hedgehog-signaling pathway were determined by immunohistochemistry and tissue microarray analyses in 36 HPV negative tumor biopsies. Expression profiles of Sonic hedgehog, Indian hedgehog, Patched, Smoothened, Gli-1, Gli-2 and Gli-3 were correlated with patients´ clinical data, local-control rate, disease-free as well as overall survival. Data from The Cancer Genome Atlas databank were used for external validation of our results.Gli-1 (p = 0.04) and Gli-2 (p = 0.02) overexpression was significantly linked to improved overall survival of HPV negative patients. Gli-2 (p = 0.04) overexpression correlated significantly with prolonged disease-free survival. Cox-multivariate analysis showed that overexpression of Gli-2 correlated independently (HR 0.40, 95% CI 0.16-0.95, p = 0.03) with increased overall survival.Gli-1 and Gli-2 overexpression represents a substantial prognostic factor for overall and disease-free survival in patients with locally advanced HPV negative head and neck cancer undergoing surgery and postoperative radiotherapy.